A method to describe attenuation of river contamination under peak flows: Can the public water supply from Paraopeba River finally return after the Brumadinho dam disaster? - de Souza Rolim, Glauco [UNESP]; Pacheco, Fernando António Leal; do Valle Junior, Renato Farias; de Melo Silva, Maytê Maria Abreu Pires; Pissarra, Teresa Cristina Tarlé [UNESP]; de Melo, Marília Carvalho; Valera, Carlos Alberto; Fernandes, Luís Filipe Sanches; Moura, João Paulo (Elsevier, 2024)
Tailings dams' disasters begin a stage of river water contamination with no endpoint at first sight. But when the river was formerly used for public water supply and the use was suspended as consequence of a dam break, a time window for safe suspension lift must be anticipated to help water managers. The purpose of this study was to seek for that moment in the case of Brumadinho dam disaster which occurred in 2019 and injected millions of cubic meters of iron- and manganese-rich tailings into the Paraopeba River, leading to the suspension of public water supply to Belo Horizonte metropolitan region with this resource, until now. To accomplish the proposed goal, an assemblage of artificial intelligence and socio-economic development models were used to anticipate precipitation, river discharge and metal concentrations (iron, manganese) until 2033. Then, the ratios of metal concentrations between impacted and non-impacted sites were determined and values representing extreme events of river discharge were selected for further assessment. A ratio ≈1 generally indicates a similarity between impacted and non-impacted areas or, put another way, a return of impacted areas to a pre-rupture condition. Moreover, when the ratio is estimated under the influence of peak flows, then a value of ≈1 indicates a return to pre-rupture conditions under the most unfavorable hydrologic regimes, thus a safe return. So, the extreme ratios were plotted against time and fitted to a straight line with intercept-x representing the requested safe time. The results pointed to 6.57 years after the accident, while using iron as contaminant indicator, or 8.71 years when manganese was considered. Despite of being a relatively low-risk timeframe, the suspension lift should be implemented in phases and monitored for precaution of potential sporadic contamination events, while dredging of the tailings from impacted areas should continue and be accelerated.
Keywords: Dam breaks; Machine learning prediction; Mine-tailings; Ratio analysis; River water contamination; Safe water supply